Numerical and experimental analysis of tension-torsion processes in cylindrical samples made of 09G2S steel under large deformations before destruction - V.G. Bazhenov; E.V. Nagornykh; D.L. Osetrov; A.A. Ryabov (Учёные записки Казанского университета: Серия Физико-математические науки)
The features of the mechanical behavior of materials under complex stress and large deformations preceding the failure is an urgent research problem. An experimental and numerical analysis of the features of the processes of elastoplastic deformation of solid cylindrical samples under proportional kinematic loading by torsion and tension up to failure has been carried out. With the joint torsion and tension action, a neck is formed. The radius of its cross section is greater and the length is smaller than in the case of pure tension. Destruction occurs along the helical surface with maximum shear deformations depending on the ratio of tension and torsion.